Effects of slalom and relay training on basketball dribbling performance in young athletes: A Pretest–posttest experimental study - Priyanto; Marcella, Gracy; Huda, Nurul; Karjadi, Moch Senoadji; Yudhistira, Dewangga (Journal Sport Area, 2026)
Background: Dribbling is a fundamental basketball skill essential for maintaining ball control and adapting to dynamic game situations. However, young athletes often demonstrate suboptimal dribbling performance, highlighting the need for effective training interventions. Although slalom and relay drills are widely used, direct experimental comparisons remain limited. Objectives: This study aimed to compare the effectiveness of slalom and relay training methods on basketball dribbling performance in young athletes. Methods: A randomized two-group pretest–posttest design was employed involving 14 male basketball players aged 11–12 years. Participants were assigned to either a slalom training group (n = 7) or a relay training group (n = 7). Both groups completed 16 training sessions over six weeks under controlled conditions. Dribbling performance was assessed using the AAHPERD test. Data were analysed using paired- and independent-samples t-tests following verification of normality and homogeneity assumptions (p > 0.05). Results: Both groups showed significant improvements in dribbling performance (slalom: p = 0.001; relay: p = 0.011). However, the slalom group demonstrated significantly greater improvement (Δ = 1.80 s) compared to the relay group (Δ = 0.87 s; p = 0.03). Conclusion: Slalom training is more effective than relay training for improving dribbling performance in pre-adolescent basketball players. These findings support motor learning theory, suggesting that training involving greater movement variability and coordinative demands enhances skill acquisition.